Strategi Pengembangan Usahatani Kakao Di Desa Mayakeli Kecamatan Pamona Puselemba Kabupaten Poso Provinsi Sulawesi Tengah - Nde'oha, Aldy Novainus; Pangemanan, Paulus Adrian; Montolalu, Maya Hendrietta (AGRI-SOSIOEKONOMI, 2024)
This research aims to identify internal and external factors in the development of cocoa farming and formulate appropriate strategies for developing cocoa plants in Mayakeli Village, Pamona Puselemba District, Poso Regency, Central Sulawesi Province. This research was carried out in Mayakeli Village, Pamona Puselemba District, Poso Regency, Central Sulawesi from June to August 2023. The method used in sampling was purposive sampling with the consideration that this area is one of the cocoa producing areas in Pamona Puselemba District. The data obtained from the interviews and questionnaires were then analyzed using SWOT analysis. The results of the research show that cocoa development in Mayakeli Village, Pamona Puselemba District, Poso Regency, Central Sulawesi is at the point (0.98 : 1.74) which is located in the Growth I quadrant.